ANALISIS TATA KELOLA SMRS PADA RS ROYAL PRIMA JAMBI MENGGUNAKAN FRAMEWORK COBIT 5.0 (FOKUS DOMAIN MEA01) - Fitri Dahlia Hutapea; Mulyadi Mulyadi; effiyaldi effiyaldi (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2021)
ABSTRACT Koperasi Unit Desa Trimulya Jaya Sungai Gelam is one cooperatives in the Jambi province which data processing savings and loan still use notebook .So there are problems data processing saving and loan that takes long time and sometimes going wrong in computational the number of saving and loan is to members, difficulty to obtain information on the saving and loan because must come to the directly, and making reports unresolved in time especially to report saving and loan report. Hence, this study aims to give solution to problem that happens by offering information systems savings loans use of language PHP programming and DBMS MySQL where is the writer expand the system with waterfall and methods used the system model unified language using use case diagram, activity diagram, class diagrams and flowchart. System information of saving dan loand at Koperasi Unit Desa Trimulya Jaya Sungai Gelam give results on the ease savings and loan data management and scored necessary spare parts and the report also ease members in see information of the transaction and apply for credit. Keywords: Information, Loans , Saving, System